Effectiveness of Foam Rolling Against Changes in Range of Motion and Pain Degree due to Delayed Onset of Muscle Soreness Post 10Km Long Distance Running in Trained Young Men - Silaban, Ebenezer; Sadhali, Muchamad; Sumirat, Nandaru Fajar; Pangestu, Bayu; Nugroho, Didit Prakosa Adi (Sports Medicine Curiosity Journal, 2022)
Delayed Onset Muscle Soreness (DOMS) is a form of injury that often occurs after training. Once, muscle experiencing DOMS the body will experience decreased muscle strength, Range of Motion (ROM), increased inflammatory response. This is a Quasi Experiment, by using the One Group Repeated-Measures Design. Providing treatment with a foam roller to the sample to see changes in ROM body functions. The results of this study indicate that there is a decrease in ROM due to DOMS post a 10Km Long Distance Running activity. the calculated reduction in this research is lower extremities, namely Joint Hip, Knee, and Ankle. The research showed that there was a change in the Range of Motion after being measured at 24 hours, 48 hours and 72 hours compared to the pre-test data. The results of this study are based on statistical tests using Repeated Measures Anova with significant of P <.05. The result of pain degree is the distribution of muscle data that feels the greatest pain in Quadriceps Femoris 70%, Tibialis Anterior 30%, Triceps Surae 30%, Gluteus 30%, and Hamstring 10%. The conclusion of this study is the effect of foam roller on increasing Range of Motion and decreasing pain level that occurs in lower extremities.